(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2019)
In this article we will examine both political and rhetorical ideas as an ideological plural and irregular set that ––at the same time–– cemented United States ideology in its early stage. The influence of this nationalist universe promoted by the Founding Fathers shaped the Presidency as a symbolic institution that has embodied, since then, an empiricism ––mostly Machiavellian, though never recognized–– moderated by a formal idealism, but only partially effective. This cultural tradition––and its contradictions–– come up to the present time, where a President such asClinton could recover the old flag of the American Dream, updating it in order to consolidate a new social liberalism.